Pengaruh Distraksi Musik Saat Pemasangan Infus Terhadap Nyeri Pada Anak Usia Sekolah (6-12 Tahun) Di IGD RSUD Majalaya - Yeni Hendriani; Fitri Komalasari (Jurnal Rumpun Ilmu Kesehatan, 2022)
Pain is a sensory and emotional experience unpleasant result of tissue damage that is actual or potential. Pain is very disturbing and difficult for many person than any disease. Music is an effective distraction technique. It has the best influence in a short time. Music reduces the physiological pain, stress and anxiety by distracting someone’s attention from the pain. Measures infusion can cause pain in school-age children. One of the ways to minimize it is the distraction of music. The research objective was to determine the effect of music distraction when infusion to pain in school-age children. The population of this study 111 person the research is a client of school-age children with a sampel of 20 respondens. Research using quasi experiment study with post test only nonequivalent control group design. The results using univariate : frequency distribution and bivariate analysis : independent t test. Distraction of music was given five minutes before to infusion for up to five minutes after the infusion. The scale of the pain felt in the control group who did not provide a distraction to music when infusion is done on 10 respondens is 60% of respondents experiencing severe pain . While the scale of perceived distraction intervention group were given music when infusion conducted in 10 respondents 20% of respondents experiencing severe pain. Evident from the results of these observation it is known that there is a significant influence on the effect of music on the infusion distraction to pain in school-age children (6-12 years) in IGD RSUD Majalaya with a significant extent (p=0,0, α=0,05). The results of this study are expected to be used as reading material and references distraction students that muaic can reduce pain.